Pengembangan Media Pembelajaran Interaktif Berbantuan Aplikasi Assemblr Edu pada Materi Teks Eksplanasi untuk Meningkatkan Higher-Order Thinking Skills (HOTS) Siswa Kelas XI - Mifta Aulia Putri; Rita Rita; Ridwan Syahputra; Rika Kartika; Ratna Soraya (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
This study aimed to develop interactive learning media assisted by the Assemblr Edu application for explanation text instruction to support the improvement of students’ Higher-Order Thinking Skills (HOTS). The study addressed the need for innovative digital learning media capable of promoting more active, engaging, and higher-level thinking-oriented learning in Indonesian language classrooms. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The population comprised 120 eleventh-grade students of SMKS MMA UISU Medan from the XI-AKL, XI-OTKP, and XI-TKJ classes, while the sample consisted of 43 students from class XI-OTKP. Data were collected through observation, questionnaires, and tests. The findings revealed that the developed interactive learning media was categorized as feasible based on material expert validation (87% and 92%), media expert validation (87% and 80%), and teacher assessment (90%). The field implementation involving 43 students obtained a feasibility score of 82.2%, while the effectiveness test reached 77.79%, indicating that the media was effective. These findings demonstrate that the Assemblr Edu-assisted interactive learning media is feasible and effective for explanation text instruction while providing a technology-based learning environment that supports the development of students’ Higher-Order Thinking Skills (HOTS).